Genome-Wide Analysis of the bHLH Gene Family in Loropetalum chinense var. rubrum: Identification, Classification, Evolution, and Diversity of Expression Patterns under Cultivation - Yang Liu; Ling Lin; Yang Liu; Qiong Mo; Damao Zhang; Weidong Li; Xingyao Xiong; Xiaoying Yu; Yanlin Li (Plants, 2023)
The basic helix–loop–helix (bHLH) transcription factor family is the second-largest transcription factor family in plants. Members of this family are involved in the processes of growth and development, secondary metabolic biosynthesis, signal transduction, and plant resistance. Loropetalum chinense var. rubrum is a critical woody plant with higher ornamental and economic values, which has been used as ornamental architecture and traditional Chinese herbal medicine plants. However, the bHLH transcription factors in Loropetalum chinense var. rubrum (L. chinense var. rubrum) have not yet been systematically demonstrated, and their role in the biosynthesis of anthocyanin is still unclear. Here, we identified 165 potential LcbHLHs genes by using two methods, and they were unequally distributed on chromosomes 1 to 12 of the genome of L. chinense var. rubrum. Based on an evolutionary comparison with proteins from Arabidopsis and Oryza sativa, these bHLH proteins were categorized into 21 subfamilies. Most LcbHLHs in a particular subfamily had similar gene structures and conserved motifs. The Gene Ontology annotation and Cis-elements predicted that LcbHLHs had many molecular functions and were involved in processes of plant growth, including the biosynthesis of flavonoids and anthocyanins. Transcriptomic analysis revealed different expression patterns among different tissues and cultivars of L. chinense var. rubrum. Many LcbHLHs were expressed in the leaves, and only a few genes were highly expressed in the flowers. Six LcbHLHs candidate genes were identified by bioinformatics analysis and expression analysis. Further Real-time quantitative PCR analysis and protein interaction network analysis showed that LcbHLH156, which is one of the candidate proteins belonging to the IIIf subfamily, could interact with proteins related to anthocyanin synthesis. Therefore, LcbHLH156 was transiently expressed in L. chinense var. rubrum to verify its function in regulating anthocyanin synthesis. Compared with the control group, red pigment accumulation appeared at the wound after injection, and the total anthocyanin content increased at the wound of leaves. These results lay a foundation for the research of the regulation mechanism of leaf colors in L. chinense var. rubrum and also provide a basis for the function of the LcbHLH family.